Required Related: Why Music And Audio Technology Courses Are Not Enough For Success In The Music Industry - Barry G Atticks; Dain Estes (Journal of the Association for Technology in Music Instruction, 2025)
This pilot study evaluates the relevance of ancillary courses (required related) in music technology curricula, emphasizing the alignment of academic offerings with industry needs. While core subjects like studio recording and sound design are well-studied, this research focuses on related courses outside the primary sequence, including technology, business, industry-specific, core music, and education courses. Surveying 20 professionals across various music technology sectors, we assessed the importance of topics such as basic electronics, wireless systems, media studies, and industrial safety. Results indicate that basic electronics and wireless systems are crucial. Media studies and industrial safety courses are also valued highly, though video production is considered less central. Business courses show mixed importance. Economics is viewed as least relevant. Music performance and theory courses receive moderate support, highlighting their value but also indicating variability based on career focus. The findings suggest curricular adjustments to enhance practical relevance and prepare students more effectively for diverse roles in the evolving music technology field.
Keywords: Curriculum; Curriculum Design; Required-Related courses; Audio Technology Education